Exploring the mass adoption potential of wearable fitness devices in Malaysia - Naeem Hayat; Anas A Salameh; Abdullah Al Mamun; Syed Shah Alam; Noor Raihani Zainol (Digital Health, 2023)
Objective The current study explores the formation of an intention to use wearable fitness devices (WFDs) with wearable fitness attributes and health consciousness (HCS). Moreover, the research examines the use of WFDs with the health motivation (HMT) and intention to use WFDs. The study also exposes the moderating effect of HMT between the intention to use WFDs and the use of WFDs. Methods Five hundred and twenty-five adults participated in the current study, and data were collected from January 2021 to March 2021 through the online survey of Malaysian respondents. The cross-sectional data was analyzed using the second-generation statistical method of partial least square structural equation modeling. Results HCS is insignificantly associated with the intention to use WFDs. Perceived compatibility, perceived product value, perceived usefulness, and perceived technology accuracy significantly influence the intention to use WFDs. HMT significantly impacts the adoption of WFDs; however, the intention to use WFDs negatively but significantly influences the use of WFDs. Lastly, the association between the intention to use WFDs and the adoption of WFDs is significantly moderated by HMT. Conclusions Our study findings illuminate the significant impact of technology-level attributes of WFDs on the intention to use WFDs. However, an insignificant impact of HCS on the intention to use WFDs was reported. Our result confirms that HMT plays a significant role in the use of WFDs. Such as the moderating role of HMT is vital to transform the intention to use WFDs into the adoption of WFDs.